Training workshop on Climate risk management in agricultural advisory services Senegal (CRMAE) - Faye, Adama (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The training workshop for technical agents on the Climate Risk Management in Agricultural Extension (CRMAE) program was organized in close collaboration with the Columbia Climate School's International Livestock Research Institute (ILRI), International Research Institute for Climate and Society (IRI), the Université du Sine Saloum Elhaddji Ibrahima Niass (USSEIN), the Université Alioune Diop de Bambey (UADB), the Agence Nationale de Conseil Agricole et Rural (ANCAR) and ISRA/ Centre d'Etudes Régional pour l'Amélioration de l'Adaptation à la Sécheresse (CERAAS). From May 08 to 16, 2023, the Thiès cluster (Méouane) was trained at the Centre d'Etudes Régional pour l'Amélioration de l'Adaptation à la Sécheresse (CERAAS) in Thies. This workshop is essential to strengthen the capacities of agricultural extension and advisory services in their role of providing support and advice to help Senegal's farmers and agro-pastoralists access, understand and integrate climate information into their professional activities. To this end, the training aims to empower beneficiaries to strengthen fundamental knowledge and skills in the areas of climate basics, climate information and tools available for agriculture, climate-sensitive agricultural decision-making and the communication and integration of climate information and services into agricultural extension. On the whole, this objective was achieved, according to the post-training survey, which showed that the course ran smoothly and the content was adapted to participants' needs. The facilitators played their role well, providing answers to participants' questions and delivering the right training content. The SIMAGRI tool, ANACIM's Maproom and GTP bulletins were among the training's highlights, as were the seasonal forecasts and the climatic service useful for decision-making. Several comments and suggestions were made to improve the organization and content of the training.